Targeted gene panel for genetic testing of south Indian children with steroid resistant nephrotic syndrome - Annes Siji; K. N. Karthik; Varsha Chhotusing Pardeshi; P. S. Hari; Anil Vasudevan (BMC, 2018)
Abstract Background Steroid resistant nephrotic syndrome (SRNS) is a genetically heterogeneous disease with significant phenotypic variability. More than 53 podocyte-expressed genes are implicated in SRNS which complicates the routine use of genetic screening in the clinic. Next generation sequencing technology (NGS) allows rapid screening of multiple genes in large number of patients in a cost-effective manner. Methods We developed a targeted panel of 17 genes to determine relative frequency of mutations in south Indian ethnicity and feasibility of using the assay in a clinical setting. Twenty-five children with SRNS and 3 healthy individuals were screened. Results In this study, novel variants including 1 pathogenic variant (2 patients) and 3 likely pathogenic variants (3 patients) were identified. In addition, 2 novel variants of unknown significance (VUS) in 2 patients (8% of total patients) were also identified. Conclusions The results show that genetic screening in SRNS using NGS is feasible in a clinical setting. However the panel needs to be screened in a larger cohort of children with SRNS in order to assess the utility of the customised targeted panel in Indian children with SRNS. Determining the prevalence of variants in Indian population and improvising the bioinformatics-based filtering strategy for a more accurate differentiation of pathogenic variants from those that are benign among the VUS will help in improving medical and genetic counselling in SRNS.